2020
DOI: 10.1111/1755-0998.13134
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide linkage map for the house sparrow (Passer domesticus) provides insights into the evolutionary history of the avian genome

Abstract: The house sparrow is an important model species for studying physiological, ecological and evolutionary processes in wild populations. Here, we present a medium density, genome wide linkage map for house sparrow (Passer domesticus) that has aided the assembly of the house sparrow reference genome, and that will provide an important resource for ongoing mapping of genes controlling important traits in the ecology and evolution of this species. Using a custom house sparrow 10 K iSelect Illumina SNP chip we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(127 reference statements)
6
12
0
Order By: Relevance
“…While we do not explicitly model LD between loci, we thus implicitly account for differences in LD across groups through the group‐specific allele effects. Hagen et al (2020) indeed found that the levels of LD in house sparrows were generally higher and remained higher over longer distances along the chromosomes on islands in our study system with smaller effective population sizes (generally outer islands, which recently went through a strong population bottleneck, see Baalsrud et al, 2014). Group‐specific allele effects can also be caused by QTL having epistatic interactions with loci whose allele frequencies differ between groups (Rio, Mary‐Huard, et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…While we do not explicitly model LD between loci, we thus implicitly account for differences in LD across groups through the group‐specific allele effects. Hagen et al (2020) indeed found that the levels of LD in house sparrows were generally higher and remained higher over longer distances along the chromosomes on islands in our study system with smaller effective population sizes (generally outer islands, which recently went through a strong population bottleneck, see Baalsrud et al, 2014). Group‐specific allele effects can also be caused by QTL having epistatic interactions with loci whose allele frequencies differ between groups (Rio, Mary‐Huard, et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…While we do not explicitly model LD between loci, we thus implicitly account for differences in LD across groups through the groupspecific allele effects. Hagen et al (2020) indeed found that levels of LD in house sparrows were generally higher and remained higher over longer distances along the chromosomes on islands in our study system with smaller effective population sizes (generally outer islands, which recently went through a strong population bottleneck, see Baalsrud et al, 2014). Group-specific allele effects can also be caused by QTL having epistatic interactions with loci whose allele frequencies differ between groups (Rio et al, 2020a).…”
Section: Wing Length Body Mass Tarsus Lengthsupporting
confidence: 64%
“…This fission was not observed in the superb fairy-wren, the sole other species from the Meliphagoidea superfamily with a chromosome-length genome that allows large-scale synteny analyses, and the high-density linkage map necessary to confirm within-chromosome linkage [ 1 ]. Neither has it been reported for other passerine birds with both resources available (i.e., great tit, collared flycatcher, and house sparrow) [ 11 , 13 , 14 ].…”
Section: Data Descriptionmentioning
confidence: 99%